Original articleEstimation of prognostic value of CD44 expression in neuroblastic tumours in children - Taran, Katarzyna; Kobos, Józef; Sitkiewicz, Anna; Sporny, Stanisław (Folia Neuropathologica, 2007)
Adversities observed in treatment of children with neoplastic disease based on new diagnostic markers and new prognostic factors. Both of them allow prognosis to be established for a single patient. The aim of our study was to examine the expression of CD44 adhesion molecule in different histologic types in a neuroblastoma group of tumours (35 cases of neuroblastoma from current files and archives) and to estimate the possible prognostic value of CD44 expression by comparison with widely accepted prognostic markers and chosen histoclinical parameters (9 cases of neuroblastoma with follow-up data). We did not find a statistically significant correlation between CD44 expression and histologic type of the tumour. However, we found that all relapses appeared among patients with tumours with the strongest CD44 expression, and that in none of the investigated tumours without relapses was strong CD44 expression ever observed. We noticed CD44 expression in 88.88% of examined tissue samples which underwent statistical analysis and we found the strongest CD44 expression in tumours situated in the retroperitoneal space. Results of log-rank test and Kaplan-Meier estimation showed that a correlation between CD44 expression and survival time was close to a statistically significant value (p=0.065). We conclude that lack of a clear statistically significant correlation between CD44 expression and histoclinical parameters and currently known prognostic factors in our study is due to the presence of many CD44 isoforms, which cannot be distinguished with commercially used antibodies, but they may play a different role in pathogenesis and spread of neuroblastoma.